Bread enriched with cricket powder (Acheta domesticus): A technological, microbiological and nutritional evaluation. (August 2018) - Osimani, Andrea; Milanović, Vesna; Cardinali, Federica; Roncolini, Andrea; Garofalo, Cristiana; Clementi, Francesca; Pasquini, Marina; Mozzon, Massimo; Foligni, Roberta; Raffaelli, Nadia; Zamporlini, Federica; Aquilanti, Lucia
Abstract: Recently, the high nutritional value of edible insects attracted the attention of researchers and food industry for their potential use in foods with enhanced nutritional characteristics. In this study cricket ( Acheta domesticus ) powder was added to wheat flour to obtain bread with enhanced nutritional value. Bread loaves were obtained from doughs produced using different blends of wheat flour and cricket powder added in amounts of 10 or 30% (based on wheat flour) and baker's yeast and/or sourdough. Raw materials, doughs and breads were subjected to technological, microbiological, chemical and sensory analyses. Overall, a negative linear correlation between the amount of added cricket powder and the dough technological parameters was seen. However, compared to control breads produced with the sole wheat flour, breads containing cricket powder showed a higher nutritional profile in terms of fatty acid composition, high protein content and occurrence of essential amino acids. Finally, bread enriched with 10% cricket powder showed a discrete global liking by untrained panelists. Data overall collected highlighted a good suitability of cricket powder for the production of enriched bread. Of note, the presence of spore-forming bacteria in cricket-based bread loaves, thus highlighting potential safety issues to be deepened. Industrial relevance: The present study demonstrated that edible insects powder can successfully be included in leavened baked goods to enhance their protein content. The present research also responds to the growing awareness of consumers towards innovative and wholesome leavened goods, proving that edible insects can constitute a novel source of innovative ingredients to be used in bread making. Highlights: Enriched bread containing cricket powder was produced. The presence of cricket powder was negatively correlated with technological features. Breads containing cricket powder showed a high nutritional profile. Enrichment in protein and essential amino acids was measured in cricket-based breads. Spore-forming bacteria in cricket-based breads highlighted potential safety issues.